Effect of Enhanced Adherence Package on Early ART Uptake Among HIV-Positive Pregnant Women in Zambia: An Individual Randomized Controlled Trial - Mubiana-Mbewe, M.; Bosomprah, S.; Kadota, J.L.; et.al (AIDS and Behavior, 2021)
We evaluated the effect of an option B-plus Enhanced Adherence Package (BEAP), on early ART uptake in a randomized controlled trial. HIV-positive, ART naïve pregnant women in Lusaka, Zambia was randomized to receive BEAP (phone calls/home visits, additional counseling, male partner engagement, and missed-visit follow-up) versus standard of care (SOC). The primary outcome was initiating and remaining on ART for 30 days. Analysis was by intention to treat (ITT) using logistic regression. An additional per-protocol analysis was done. We enrolled 454 women; 229 randomized to BEAP and 225 to SOC. Within 30 days of eligibility, 445 (98.2%) initiated ART. In ITT analysis, 82.5% BEAP versus 80.4% SOC participants reached the primary outcome (crude relative risk [RR] 1.03; 95% confidence interval [CI] 0.91–1.16; Wald test statistic = 0.44; p-value = 0.66). As per protocol analysis, (92 participants (40.2%) were excluded), 91.9% BEAP versus 80.4% SOC participants reached primary outcome (crude RR 1.14; 95% CI 1.02–1.29; Wald test statistic = 2.23; p-value = 0.03). Early ART initiation in pregnancy was nearly universal but there was an early drop out suggesting the need for additional adherence support.
Research Article
Keywords: HIV seropositivity; Pregnant women; Antiretroviral therapy; Option B + uptake; Enhanced adherence